Usefulness of cash flow indicators in credit analysis: Case of Serbia - Stevanović Slavica (Bankarstvo, 2018)
The aim of this paper is to analyze the representation and usefulness of cash flow indicators in the credit analysis process in Serbia. The research methodology includes the content analysis taken for the research purpose. Key contributions of the paper are empirical research based on scientific surveys. The credit analysis practice in Serbia has been studied regarding the application of cash flow based financial indicators in the system of assessing the credit rating of the banks' business credit users. The research results indicate that cash flow-based indicators are less widely used in credit ratings compared to indicators based on balance sheet and income statement items. Nevertheless, surveyed credit analysts in Serbia confirm the usefulness of cash flow information of banks' clients for making credit decisions. Liquidity indicator based on cash flow, selected coverage indicators and cash flow margin record the highest representation and usefulness of the application in the credit rating system of business clients among selected cash flow indicators.